The effect of spillovers and congestion on the segregative properties of endogenous jurisdiction structure formation - Rémy Oddou (Fondazione Eni Enrico Mattei (FEEM), 2011)
This paper analyzes the effect of spillovers and congestion of local public goods on the segregative properties of endogenous formation of jurisdiction. Households living in the same place form a jurisdiction and produce a local public good, that creates positive spillovers in other jurisdictions and suffers from congestion. In every jurisdiction, the production of the local public good is financed through a local tax on household's wealth. Local wealth tax rates are democratically determined in all jurisdictions. Households also consume housing in their jurisdiction. Any household is free to leave its jurisdiction for another one that would increase its utility. A necessary and sufficient condition to have every stable jurisdiction structure segregated by wealth, for a large class of congestion measure and any spillovers coefficient structure, is identified: the public good must be a gross substitute or a gross complement to the private good and the housing.
Keywords: C78; D02; H73; R13; 330; Jurisdictions; Segregation; Spillovers; Congestion